Circadian rhythms and the liver. (11th January 2023) - Costa, Rodolfo; Mangini, Chiara; Domenie, Esther D.; Zarantonello, Lisa; Montagnese, Sara
Abstract: This narrative review briefly describes the mammalian circadian timing system, the specific features of the liver clock, also by comparison with other peripheral clocks, the role of the liver clock in the preparation of food intake, and its relationship with energy metabolism. It then goes on to provide a chronobiological perspective of the pathophysiology and management of several types of liver disease, with a particular focus on metabolic‐associated fatty liver disease (MAFLD), decompensated cirrhosis and liver transplantation. Finally, it provides some insight into the potential contribution of circadian principles and circadian hygiene practices in preventing MAFLD, improving the prognosis of advanced liver disease and modulating liver transplantation outcomes.